Tunisia : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper analyzes trends in Tunisian inflation. It computes measures of core inflation, and develops a simple framework for forecasting inflation. The paper econometrically estimates the degree of exchange rate pass-through in Tunisia. The methodology relies on time series and panel estimation methods, using both monthly and quarterly data for a basket of 43 consumption products during 1995-2006. It summarizes the results of some empirical studies on developing and emerging economies. It also describes the fluctuations in the nominal effective exchange rate in Tunisia and the resulting effects on inflation.